(untitled) (Proceedings of Southern Federal University. Philology, 2026)
10.18522/1995-0640-2026-1-96-108 The study is devoted to a linguo-pragmatic analysis of the title of Jane Austen’s novel “Pride and Prejudice” as a binary authorial opposition that sets the vector for reader interpretation. Drawing on lexicographic sources, the synonymous range of the interacting key lexemes (pride and prejudice) is examined, and their semantic nuances are established as the foundational material for identifying the textual semantization of the titular nominations as the primary authorial interpretation of the work. The analysis employed the techniques of functional-pragmatic, definitional, contextual, and comparative methods. The examination of the historical and cultural context revealed the linguo-pragmatic features, as well as the specifics of the title’s phonetic and grammatical organization. The modeling of textual synonymic paradigms demonstrates the individual-authorial semantization of the titular nominations through synonymic variation, attraction, and semantic nuance, which serve as a pragmatic tool for realizing the author’s intent. Key words: title semantics, Jane Austen, authorial intent, character portrayal, artistic reflection, synonymic paradigm, synonymic variation